The tricuspid valve in hypoplastic left heart syndrome: Echocardiography provides insight into anatomy and function - Bharucha, Tara; Viola, Nicola (Frontiers in Pediatrics, 2023)
Tricuspid regurgitation (TR) is commonly seen in surgically palliated patients with hypoplastic left heart syndrome, and when significant, is associated with an increase in both morbidity and mortality. Tricuspid valve dysfunction appears to be the result of a combination of inherent structural malformations and the unique physiological circumstances resulting from right ventricular pressure and volume overload. Valve dysfunction evolves rapidly, and manifests early on in the surgical pathway. Whilst traditional echocardiographic imaging can identify anatomical defects and dysfunction resulting in varying degrees of regurgitation even at early stages, more sophisticated investigations such as 3D echocardiography, strain imaging and transesophageal 3DE might prove useful to better demonstrate the complex interactions between abnormal anatomy of the valve complex, ventricular function, mechanical synchrony, and TR. Recognition of specific mechanisms of TR can enhance patient-specific care by directing precise surgical interventions and by informing the best timing for intervention on the valve.